Airway changes following labor and delivery in preeclamptic parturients: a prospective case control study. (February 2018) - Ahuja, P.; Jain, D.; Bhardwaj, N.; Jain, K.; Gainder, S.; Kang, M.
Highlights: Airway changes persist untill 48 hours postpartum. Prolonged labor is associated with changes in airway dimensions. Ultrasonography can help to detect a difficult airway in a laboring parturient. Abstract: Background: Preeclampsia is associated with greater narrowing of the airway than normal pregnancy, but it is not known if these changes worsen during labor and delivery. The aim of the study was to evaluate the airway during and after labor in women with or without preeclampsia. Methods: Twenty-five normal and 25 severely preeclamptic pregnant women in early labor were recruited in this single-center, prospective, case-control study. Airway assessment was performed (a) before active labor (b) within one hour of delivery and (c) 24–48 h postpartum. The Mallampati grade was the primary outcome. Sonographic measurements of tongue thickness, anterior neck soft tissue at the level of the hyoid bone and the vocal cords, thyromental distance, and neck circumference, were secondary outcomes. Results: The Mallampati score increased from the pre-labor to the post-labor period in both preeclamptic and normotensive patients ( P =0.001 and P =0.002 respectively). A significant difference in tissue thickness at the hyoid level was observed between preeclamptic and normotensive patients pre-labor ( P =0.035), post-labor ( P =0.05) and postpartum ( P =0.05). There was no significant difference in thyromental distance or neck circumference between groups at any time. The total duration of labor and a Mallampati change by one grade correlated (Spearman correlation coefficient 0.473). Conclusion: Airway sonography may provide useful bedside anatomical information for prediction of difficult laryngoscopy. The change in airway dimensions and the Mallampati score during labor may persist for 48 h postpartum in both groups. Those with prolonged labor are more susceptible to changes in airway dimensions.